2013
DOI: 10.1080/17461391.2013.775351
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of a cluster-set protocol on hormonal, metabolic and performance measures in resistance-trained males

Abstract: Limited research exists on rest-pause or cluster-set (CS) protocols. Acute effects of a traditional set (TS) and CS protocols of resistance exercise on serum growth hormone (GH), cortisol (C), blood lactate (BL), countermovement vertical jump (CMVJ) and standing long jump (SLJ) were compared. Eleven resistance-trained males (22.9 ± 2.6 year; 176.9 ± 10.6 cm; 78.5 ± 1.6 kg; 12.9 ± 3.1% BF) completed one repetition maximum tests for clean pull (CP), back squat (BS) and bench press (BP). Subjects were then random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 27 publications
5
52
4
Order By: Relevance
“…In the current study, cortisol increased in a linear fashion in the TRD condition, remaining elevated 30 min post-exercise, while a lesser slope of increase was observed in CLU achieving only one value (15 min) above baseline values. This is in disagreement with Girman et al (2014) in which the authors reported a similar cortisol response for both CLU and TRD conditions. The similar high lactate values and accompanying pattern of growth hormone observed immediate post-exercise in that study likely contributed to the divergent findings.…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…In the current study, cortisol increased in a linear fashion in the TRD condition, remaining elevated 30 min post-exercise, while a lesser slope of increase was observed in CLU achieving only one value (15 min) above baseline values. This is in disagreement with Girman et al (2014) in which the authors reported a similar cortisol response for both CLU and TRD conditions. The similar high lactate values and accompanying pattern of growth hormone observed immediate post-exercise in that study likely contributed to the divergent findings.…”
Section: Discussioncontrasting
confidence: 73%
“…TUT was not controlled during the current study, but TUT in Set 4 was 2.43 ± 0.09 and 2.26 ± 0.09 s in the TRD and CLU condition, respectively. In the study conducted by Girman et al (2014), TUT was controlled in a 2-0-2 tempo, providing for more than 1.5 s longer TUT than that reported in the current study. Further studies are necessary to examine the potential differences in effect of TUT and lactate on the growth hormone response following exercise.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations